An Intercountry Translog Model of Energy Substitution Responses - Griffin, James M.; Gregory, Paul R. (American Economic Review, 1976)
Results of earlier transcendental logarithmic (translog) production function are challenged on the basis of the limited time-series used. The same methodology is applied to a pool of international manufacturing data to test whether long-run price elasticities can be generated with intercountry samples. Both the time-series and international cross-section methods agree that there is some elasticity of substitution between energy demand and non-energy inputs and that energy forecasting should not be based on the assumption that substitutions between energy and nonenergy inputs are trivial. The international method finds, however, that capital and energy are substitutes rather than complements in the long-run and that there is a difference between short-run and long-run effects of substitution. 29 references. (DCK)